An evaluation of craniofacial growth pattern in North Indian children - Vivek Mehta; R.K. Pandey (Journal of Oral Biology and Craniofacial Research)
Objective: The aim of this study was to assess craniofacial growth pattern in children with generalized decreased skeletal age and compare it with the children having normal skeletal age. Materials and methods: Lateral cephalograms and hand wrist radiographs of 40 patients (age group 3–14 years) were taken and skeletal age assessment was done with hand wrist radiographs according to Greulich and Pyle, based on which two groups were made, Group A – Control group (normal skeletal age) and Group B – study group (decreased skeletal age). Group A had a sample size of 21 and Group B, a sample size of 19. These were further divided into subgroups according to age: subgroup (a) – 3 to 6 years, subgroup (b) – 7 to 11 years and subgroup (c) – 12 to 14 years. The skeletal and dental patterns were analyzed with Down's Cephalometric analysis. Student “t” test was used to verify comparisons in all the subgroups of patients of Group A and Group B. Results: The facial angle and Cant of occlusal plane exhibited maximum difference between the two groups which indicated that mandibular growth was affected more than other bones in diseased child patients. Conclusion: The present study led to the conclusion that craniofacial growth was retarded in children with generalized decreased skeletal age in comparison to healthy child patients.